Analisis Ketercapaian Standar Sarana dan Prasarana pada Sekolah Menengah Pertama di Bekasi - Megawati, Megawati; Rochman, Chaerul (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2019)
This article aims to determine the achievement of educational facilities and infrastructure standards at SMP ISLAM AL-AMIN Cikarang Bekasi. This research is qualitative research: Case Study by collecting data in the form of observation, interviews and documentation. The results of this study indicate that the achievement of standard facilities and infrastructure at SMP ISLAM AL-AMIN Cikarang Bekasi amounted to 92.5% when compared with the entire maximum score that should be achieved in the form of standard facilities and infrastructure. This study recommends exploring the indicators that have not been optimally achieved, especially indicators of providing guidance and counseling space, UKS and laboratories. Although it feels good, but empowerment, utilization and maintenance of facilities and infrastructure in schools must be improved. This is intended to improve the quality of education and satisfaction of community expectations.Keywords:Profile of indicators achievement, Standard of facilities & infrastructure.